2023
DOI: 10.1900/rds.2023.19.14
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-ratio Combinations (basal Insulin Plus GLP-1RA) In Type 2 Diabetes. an Analytical Review Of Pivotal Clinical Trials

Abstract: In type 2 diabetes, therapeutic failure to the oral anti diabetics is frequent, the use of schemes with basal insulin or with multiple doses of insulin (basal insulin and short-acting insulins) are a widely accepted way to intensify therapy. The use of GLP-1 receptor agonists is another intensification strategy. The fixedratio combinations with molecules such as insulin degludec + liraglutide, and insulin glargine + lixisenatide have proven useful in intensifying treatment of individuals with type 2 diabetes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…LixiLan trial with iGlarLixi and Dual trial with iDegLira had shown that aforementioned medications had good potency and e cacy regarding glycemic parameters (4,5,10). Recent studies have shown good glycemic control and safety pro le with xed combination in comparison to intensi cation of oral antidiabetics with premix insulins or addition of prandial insulin in patients previously uncontrolled with basal insulin (17)(18)(19). Bilic Curcic et al have shown that in T2DM patients poorly controlled on different insulin regimens, switching to either one of the available xed ratio combination bene ted glycemic control (2).…”
Section: Discussionmentioning
confidence: 99%
“…LixiLan trial with iGlarLixi and Dual trial with iDegLira had shown that aforementioned medications had good potency and e cacy regarding glycemic parameters (4,5,10). Recent studies have shown good glycemic control and safety pro le with xed combination in comparison to intensi cation of oral antidiabetics with premix insulins or addition of prandial insulin in patients previously uncontrolled with basal insulin (17)(18)(19). Bilic Curcic et al have shown that in T2DM patients poorly controlled on different insulin regimens, switching to either one of the available xed ratio combination bene ted glycemic control (2).…”
Section: Discussionmentioning
confidence: 99%